2020
DOI: 10.1177/1049732320969395
|View full text |Cite
|
Sign up to set email alerts
|

Sick of the Sick Role: Narratives of What “Recovery” Means to People With CFS/ME

Abstract: Little is known about what recovery means to those with chronic fatigue syndrome/myalgic encephalomyelitis, a poorly understood, disabling chronic health condition. To explore this issue, semi-structured interviews were conducted with patients reporting improvement ( n = 9) and deterioration ( n = 10) after a guided self-help intervention, and analyzed via “constant comparison.” The meaning of recovery differed between participants—expectations for improvement and deployment of the sick role (and associated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Such a concept has been used effectively regarding counter narratives to “aging is decline” (e.g., Phoenix & Sparkes, 2006), and can be effective regarding aging with MS. By showing Jane’s story including how she “ages well” and manages different symptoms, this may inform persons with MS that there are affirming ways to age with MS, with some suggestions of how to do so. Furthermore, we show a way through Jane’s management of her symptoms that she was able to craft a sense of self-hood (Maietta, 2021) that was more empowering to her rather than a “sick role” (Cheshire et al, 2021) which dominate social narratives of MS. Amplifying and promoting this narrative to individuals who mirror the MS trajectory of Jane (i.e., mild to moderate symptoms, relatively stable relapses) may address concerns regarding solely negative portrayals of aging with MS being available. As such, this experience may not be something to be feared.…”
Section: Discussion and Recommendationsmentioning
confidence: 97%
“…Such a concept has been used effectively regarding counter narratives to “aging is decline” (e.g., Phoenix & Sparkes, 2006), and can be effective regarding aging with MS. By showing Jane’s story including how she “ages well” and manages different symptoms, this may inform persons with MS that there are affirming ways to age with MS, with some suggestions of how to do so. Furthermore, we show a way through Jane’s management of her symptoms that she was able to craft a sense of self-hood (Maietta, 2021) that was more empowering to her rather than a “sick role” (Cheshire et al, 2021) which dominate social narratives of MS. Amplifying and promoting this narrative to individuals who mirror the MS trajectory of Jane (i.e., mild to moderate symptoms, relatively stable relapses) may address concerns regarding solely negative portrayals of aging with MS being available. As such, this experience may not be something to be feared.…”
Section: Discussion and Recommendationsmentioning
confidence: 97%
“…Along those lines, according to Optimal Matching Theory (24), social support is maximized when the need for support and the provision of support are aligned (22). Alternatively, when need and provision of support are not aligned, social support may be not only not bene cial but perhaps harmful by perhaps promoting "sick role" behavior as opposed to promoting recovery (23). Thus, SRCE may be a model for helping patients to understand the interpersonal dynamics of social support and advocate for their need for support as well as to be able to help others understand that mismatched support provision may not be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with the best of intentions on the part of the support-giver, there may be detrimental effects of a mismatch between the need for support and the support provided (22). This mismatch may take for form of not only neglecting to provide the support that was needed but also providing support when it is not needed, thereby undermining the patient's personal agency concerning self-care and reinforcing "sick role" behavior (23).…”
Section: Introductionmentioning
confidence: 99%
“…Such total withdrawal is problematic as social isolation may be a predictor of prolonged absence (Steenstra et al, 2005). Recent research has also indicated that freedom from the 'sick role' can be an important part of recovery for patients with chronic illness (Cheshire et al, 2021). RTW professionals may thus have an important role in reinforcing health promoting behaviors when such behaviors appear to contradict what is expected in the sick role.…”
Section: Discussionmentioning
confidence: 99%